The effect of technological stress dimensions on employees' decision-making styles and regulatory role of job insecurity perception: a research in the aviation sector - BÖRÜ, MELİHA DENİZ (My University, 2023)
The technological stress factor is more evident in the aviation industry, which uses high and rapidly changing technology, especially for technical employees. The purpose of this research is to determine the effect of technostress levels of aviation industry employees on their decisionmaking styles and to analysis the regulatory effects of job insecurity perception, which is of great importance for businesses and employees in this effect. The research universe has been determined as the technical personnel in the airline companies operating in Turkey. In all, 402 questionnaires were considered valid and included in the 25th data analysis of SPSS. It was determined that technological stress was statistically significantly related to rational, intuitive, avoidant and instant decision-making. Meanwhile, each decision-making style and the dimensions of job insecurity perception separately have significant moderator roles. Finally, it was revealed that all technostress dimensions, except for the techno-invasion dimension, were statistically significantly correlated with at least one decision-making style. In the research, suggestions were made for the effects of changes in employee’s decision-making styles and perceptions of job insecurity as a result of the effects of technostress, and the results were tried to be explained with aviation industry dynamics and theoretical literature.
Keywords: Sosyal ve Beşeri Bilimler; İşletme; Yönetim ve Organizasyon; İşletme Yönetimi; Yönetim ve Yönetici Geliştirme; Social Sciences and Humanities; Management; Management and Organization; Management of Enterprises; Management and Manager Development; Sosyal Bilimler (SOC); Ekonomi ve İş; İŞLETME; YÖNETİM; Social Sciences (SOC); ECONOMICS & BUSINESS; BUSINESS; MANAGEMENT; Karar Bilimleri (çeşitli); Genel Karar Bilimleri; Strateji ve Yönetim; Pazarlama; İşletme ve Uluslararası Yönetim; Genel İşletme, Yönetim ve Muhasebe; Sosyal Bilimler ve Beşeri Bilimler; Decision Sciences (miscellaneous); General Decision Sciences; Strategy and Management; Marketing; Business and International Management; General Business, Management and Accounting; Social Sciences & Humanities